2011
DOI: 10.1002/rcm.5009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of illicit drugs on surfaces using direct analysis in real time (DART) time‐of‐flight mass spectrometry

Abstract: Methamphetamine (meth) from meth syntheses or habitual meth smoking deposited on household surfaces poses human health hazards. The U.S. State Departments of Health require decontamination of sites where meth was synthesized (meth labs) before they are sold. National Institute for Occupational Safety and Health (NIOSH) methods for meth analysis require wipe sampling, extraction, clean-up, solvent exchange, derivatization, and/or mass spectral analysis using selected ion monitoring. Rapid and inexpensive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 9 publications
0
57
0
Order By: Relevance
“…A range of analytical methods have been used in the measurement of contamination (on surfaces and in different materials) associated with clandestine laboratories (157,(160)(161)(162)(163)(164)(165)(166).…”
Section: Sampling and Analysis Issuesmentioning
confidence: 99%
“…A range of analytical methods have been used in the measurement of contamination (on surfaces and in different materials) associated with clandestine laboratories (157,(160)(161)(162)(163)(164)(165)(166).…”
Section: Sampling and Analysis Issuesmentioning
confidence: 99%
“…The usefulness of this technique in forensic analysis of illegal drugs [like cocaine, tetrahydrocannabinol (THC), opioids, psilocin, etc.] was demonstrated before [28], and DART-MS is now a well established direct technique to screen complex biological matrices for synthetic cannabinoids, enabling a rapid and sensitive analysis overview without the need for sample extraction [29]. However, under these conditions, DART-MS is a preliminary qualitative screening method and cannot provide accurate quantitation data, because the illicit drugs are usually distributed very inhomogeneously in the herbal products [30].…”
Section: Esi-ms/ms Quantificationmentioning
confidence: 99%
“…45,48 DART analysis has been applied successfully in the majority of applications where other ambient mass spectrometry methods have been utilized. 11,21,47,49 The selection of DESI or DART as the ionization source for a particular analytical application requires consideration of the target analyte's solubility in potential DESI spray solvents, and vapor pressure as well as potential reactivity in known DART ionization mechanisms. Prior work has shown that DART analysis can be readily applied to applications with highly complex sample compositions.…”
mentioning
confidence: 99%